IDENTIFICATION OF FORMALIN CONTENT IN ANCHOVY SALTED FISH SOLD IN SEVERAL TRADITIONAL MARKETS IN BANDUNG CITY - Junianto Junianto; Lina Karlina (Jurnal Perikanan Unram, 2024)
Formalin is one of the preservatives that are dangerous when added to food. However, its use is still widely carried out by irresponsible producers, one of which is in anchovies. This study aims to analyze the presence or absence of formalin content in anchovy salted fish sold in several traditional markets in Bandung. The formalin test method was carried out qualitatively and quantitatively using a nash reagent and a spectrophotometer UV-Vis. The results of research on anchovy salted fish samples from Gedebage Market, Caringin Market, Simpang Dago Market, and Kosambi Market found the presence of formalin in all samples with the highest content in anchovy samples obtained from Gedebage Market, which was 7,14 mg/l.